Role of hemithyroid preservation in total laryngectomy for laryngeal/hypopharyngeal malignancy - Premachandran, Architha Menon; Ramaswamy, Balakrishnan; Devaraja, K.; Pujary, Kailesh; Nayak, Dipak Ranjan (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2022)
Background: Thyroid gland invasion in advanced laryngeal/hypopharyngeal malignancy is not uncommon. The preservation of the contralateral lobe of thyroid and associated parathyroid glands with its blood supply, in suitable patients, can be beneficial in reducing the incidence of both hypothyroidism and hypoparathyroidism. The aim of the study was to assess the functionality of the contralateral preserved hemi-thyroid gland with its parathyroid glands, during total laryngectomy with or without partial/total pharyngectomy (TL/TLP), with or without post-operative radiation therapy. Methods: A retrospective study of patients with advanced laryngeal or hypopharyngeal malignancy who underwent TL/TLP with contralateral hemi-thyroid and parathyroid gland preservation, between January 2012 and May 2019 were included in this study. Pre-operative thyroid/parathyroid function was assessed by estimation of blood levels of T3, T4, TSH and calcium. The same were evaluated at 1week and 6 weeks following surgery and 4 weeks following radiotherapy. Results: 72.7% patients developed hypothyroidism and only 22.7% developed hypocalcemia following surgery alone at the end of 6 weeks post-surgery. 60% developed hypothyroidism and 10% had hypocalcemia in the group of patients who underwent surgery followed by radiotherapy. Conclusions: Preservation of contralateral hemi-thyroid with parathyroid glands, significantly reduces the incidence of hypoparathyroidism in patients undergoing TL/TLP. Though incidence of hypothyroidism in such cases is still high, reduced dose of thyroid hormone supplementation was achieved. Post-operative radiotherapy did not significantly alter the thyroid and parathyroid function in such cases.